'phan yul gyi gnas bshad ngo mtshar rig gnas kyi bang mdzod - bSod-nams-chos-dar (mi rigs dpe skrun khang, 2009)
Guidebook to the region of Phen, a valley close to and north of Lhasa
Keywords: Lhasa; Führer